Disabling interpretations : the Americans with Disabilities Act in federal court - Mezey, Susan Gluck, 1944- (University of Pittsburgh Digital Collections., 2005)
"Susan Mezey argues that the Americans with Disabilities Act (ADA) of 1990 has not fulfilled its potential primarily because of the judiciary's "disabling interpretations" in adjudicating ADA claims. In a decade of litigation, judicial interpretation of the law has largely constricted the parameters of disability rights and excluded large numbers of claimants from the reach of the law. The Supreme Court has not interpreted the act broadly, as was intended by Congress, and this method of decision making has been for the most part mirrored by the courts below.